The determinants of life quality in African countries: Moderating role of CO2 emissions and health expenditures - Nazife Özge Beşer; Meral Çabaş; Süleyman Uğurlu; Cosimo Magazzino (Green Technologies and Sustainability, 2025)
The aim of the study is to examine the determinants of quality of life in some African countries using carbon dioxide (CO2) emissions and health expenditures. For this purpose, annual data for the period 2000–2019 were considered for 20 African countries, and the Generalized Method of Moments (GMM) estimator was used in the analysis. In the study, second-generation panel tests were applied, considering the cross-sectional dependence and heterogeneity of the variables. The Durbin–Hausman cointegration test revealed that there was a long-term relationship between the variables; the size and direction of this relationship were analyzed with the GMM method. The findings obtained from the study reveal three important results. First, carbon dioxide emissions (CO2) and urbanization (URB) negatively affect the quality of life by reducing life expectancy at birth in the long-run. Second, increases in health expenditures (HEALTH) and per capita income (GDP) significantly improve quality of life. Third, a strong causal relationship from health expenditures to quality of life emphasizes the importance of health investments. To improve the quality of life, reducing carbon emissions Sustainable Development Goal (SDG) 13 – “Climate Action” and improving access to health services SDG 3 – “Good Health and Well-being” are priorities. Expanding the use of renewable energy, adopting policies to reduce environmental pollution, and integrating green technologies into industry are necessary.